Checkpoint inhibitors for malignant melanoma: a systematic review and meta-analysis - Karlsson, Adam K (Clin Cosmet Investig Dermatol, 2017)
BACKGROUND AND OBJECTIVES: Rates of malignant melanoma are continuing to increase, and until recently effective treatments were lacking. However, since 2011 three immunotherapeutic agents, known as checkpoint inhibitors, have been approved. This review aims to establish whether these three drugs – ipilimumab, nivolumab, and pembrolizumab – offer greater efficacy and tolerability compared to control interventions (placebo, immunotherapy, or chemotherapy) in patients with stage III or IV unresectable cutaneous melanoma. MATERIALS AND METHODS: A search on four major medical and scientific databases yielded 7,553 records, of which seven met the inclusion criteria, with a total study population of 3,628. Only prospective Phase II or III randomized controlled trials on checkpoint inhibitors for patients with unresectable cutaneous melanoma that reported data on survival (overall or progression-free), tumor response, or adverse events were included. Three meta-analyses were carried out. RESULTS: The hazard ratio for progression or death was 0.54 (95% confidence interval [CI]: 0.44–0.67), and the odds ratio for best overall response rate was 4.48 (95% CI: 2.77–7.24), both in favor of checkpoint inhibitors. However, control treatments were associated with an insignificantly lower rate of discontinuation of treatment due to adverse effects or treatment-related adverse events (odds ratio =1.63 [95% CI: 0.55–4.88]). CONCLUSION: This study finds that checkpoint inhibitors are more effective than control interventions, both in terms of survival and tumor response, and yet no less tolerable. PD1 therapies (nivolumab and pembrolizumab) appear to offer greater efficacy than CTLA4 therapy (ipilimumab). The combination of nivolumab and ipilimumab was, however, the most effective, but significantly less tolerable than monotherapy. The lack of published clinical data does, however, limit this study. Further research is needed in two areas in particular: 1) to determine the optimal use of checkpoint inhibitors, specifically in terms of combination therapy, and 2) to identify reliable biomarkers to predictive responders and guide treatment assignment.